Clinical utility of nanopore-targeted sequencing for diagnosing and treating pulmonary infectious diseases from bronchoalveolar lavage fluid - Li, Gen; Sun, He; Ye, Yangqin; Chen, Liqiong; Zhang, Wenyan; Yu, Shanshan; Li, Qiang; Fan, Lieying (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundConventional microbial testing (CMTs) for infectious pathogens faces challenges in rapid and comprehensive detection. Nanopore-targeted sequencing (NTS) is a novel approach for rapid identification of pathogens; however, clinical experience with the application of NTS is limited.MethodsWe evaluated the diagnostic value of NTS for detecting microbes in bronchoalveolar lavage fluid samples in patients with pulmonary infectious disease (PID, 137 cases), non-pulmonary infectious disease (NPID, 32 cases), or with an unknown etiology (11 cases). We performed a comparative analysis of the diagnostic efficacy of NTS and CMTs in identifying pulmonary infectious diseases and investigated the clinical utility of NTS as a diagnostic tool.ResultsNTS was significantly more sensitive than CMTs in detecting PID (86.13% vs 67.15%, P < 0.01), particularly for important specific pathogens. There were no significant differences between NTS and CMTs in terms of specificity, positive predictive value or negative predictive value. Moreover, NTS (not CMTs) detected 56 microorganisms consistent with clinical presentation, indicating that NTS can provide clinicians with additional support for infection diagnosis. Additionally, prior antibiotic exposure had no influence on the detection efficiency of NTS but significantly hindered that of CMTs. After antibiotic adjustments based on NTS findings, 87.76% of patients showed significant improvement, with a notable decrease in the level of inflammatory markers (CRP, NP, PCT, WBC) post-treatment. Furthermore, NTS can significantly shorten turnaround time and provide real-time results for rapid decision making.ConclusionsNTS is more efficient than CMTs in diagnosing pulmonary infectious diseases, particularly in detecting critical or specific pathogens, providing faster and more accurate clinical information even for patients with prior antibiotic exposure. Moreover, NTS can assist clinicians in formulating more effective anti-infection strategies.